Virotyping and genetic antimicrobial susceptibility testing of porcine ETEC/STEC strains and associated plasmid types - Nick Vereecke; Sander Van Hoorde; Daniel Šperling; Sebastiaan Theuns; Bert Devriendt; Eric Cox (2023)
Enterotoxigenic